Susceptibility of livestock to SARS-CoV-2 infection - Angela M. Bosco-Lauth; Audrey Walker; Lauren Guilbert; Stephanie Porter; Airn Hartwig; Emma McVicker; Helle Bielefeldt-Ohmann; Richard A. Bowen (Emerging Microbes and Infections)
We report pilot studies to evaluate the susceptibility of common domestic livestock (cattle, sheep, goat, alpaca, rabbit, and horse) to intranasal infection with SARS-CoV-2. None of the infected animals shed infectious virus via nasal, oral, or faecal routes, although viral RNA was detected in several animals. Further, neutralizing antibody titres were low or non-existent one month following infection. These results suggest that domestic livestock are unlikely to contribute to SARS-CoV-2 epidemiology.